Effect of elemental sulphur timing and application rates on soil P release and concentration in maize - Karimizarchi, Mehdi; Husin, Aminuddin; Yusop, Mohd Khanif; Othman, Radziah (Universiti Putra Malaysia Press, 2016)
High pH soil accounts for more that 30 percent of world's soils and poses problems to plant nutrient availability. As a cheap and readily available source of soil acidulates, elemental sulphur may be a useful material for alleviating some alkaline soil problems. To elucidate the role of elemental sulphur as a soil amendment for plant production in a high pH soil, maize plants were grown under greenhouse conditions for 45 days after 0, 20 and 40 days of soil incubation at different rates of elemental sulphur (0, 0.5, 1 and 2 g S kg-1 of soil). Soils were sampled two times (before and after planting) and subjected to soil pH and available P determination. The results showed with each unit increase in S rate, soil pH decreases by 1.52 units. In addition, while sulphur application increased available P before planting, it failed to increase P supply to maize at harvest. Supporting the role of elemental S on soil P availability, with increasing S application rate the P concentration in maize root, stem and leaves was successively decreased. This relationship can be explained by the dilution of P in increasing leaf biomass and the similar concomitant increase of both zinc and manganese nutrient concentrations with increasing sulphur application rate. Overall, soil acidification by elemental sulphur application resulted in P reduction in soil labile pools and intensified P deficiency in maize.